Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I would really appreciate some help with proving following identity. I've been trying for the whole day to no avail.

$\ \displaystyle\sum_{i = 0}^{[n/2]} \binom {n} {2i} p^{2i}q^{n-2i} = \frac{1}{2}[(p+q)^n + (q-p)^n ]$

Where by$\ [n/2]$ we mean the largest integer less than or equal to $\ n/2 $. Also $\ q = 1 - p$

This question is a step in a probability problem that i'm solving hence the $\ q = 1 - p $.

share|improve this question
Have you tried expanding both $(q+p)^n$ and $(q+(-p))^n$ using the binomial theorem? –  dtldarek Sep 14 '13 at 18:58
Please, use $\large\left\lfloor n/2\right\rfloor$ instead of $\large\left\lbrack n/2\right\rbrack$. –  Felix Marin Sep 14 '13 at 19:13

2 Answers 2

up vote 0 down vote accepted

Expand the righthand side:

$$\begin{align*} \frac12\left((p+q)^n+(-p+q)^n\right)&=\frac12\left(\sum_{k=0}^n\binom{n}kp^kq^{n-k}+\sum_{k=0}^n\binom{n}k(-1)^kp^kq^{n-k}\right)\\\\ &=\frac12\sum_{k=0}^n\binom{n}k\left(1+(-1)^k\right)p^kq^{n-k}\\\\ &=\frac12\sum_{k=0}^{\lfloor n/2\rfloor}\binom{n}k2p^{2k}q^{n-2k}\\\\ &=\sum_{k=0}^{\lfloor n/2\rfloor}\binom{n}kp^{2k}q^{n-2k}\;, \end{align*}$$

since $$1+(-1)^k=\begin{cases}2,&\text{if }k\text{ is even}\\0,&\text{if }k\text{ is odd}\;.\end{cases}$$

share|improve this answer

From $$(q\pm p)^n=\sum_{j=0}^n{n\choose j}(\pm 1)^{j}p^jq^{n-j} $$ we see that adding both sums cancels all terms with odd $j$. After halving the sum and replacing even $j$ with $2i$, we obtain the desired result.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.